Analysis Of Learning Obstacle On Fraction Material for Grade V Elementary School Students - Chandra Sagul Haratua; Erwinsyah; Heru Suparman; Megawati (Global Action and Education for Society, 2025)
This research intends to examine how the management of learning strategies in economics-based social sciences (IPS) can enhance the economic competence of high school students. This study was done with qualitative approaches using literature study and observation methods. The study was conducted at SMA Negeri 3 South Jakarta involving 45 IPS teacher respondents and 150 student respondents. They collected data using questionnaires, classroom observations, and interviews and then analyzed them qualitatively and quantitatively. The research findings show that the implementation of structured and innovative learning can improve students’ understanding, interest and critical thinking of economical concept. Teachers' managerial strategies consist of planning, organizing, implementing, controlling, and evaluating learning. An effective and productive learning environment happens with these managerial strategies. Teachers who use a very clear learning plan (82%) and organize learning activities well (76%) are effective. Teachers who manage time and discipline well (88%) and often give evaluation and feedback (15%) increase in students average grades) are effective. The findings of this research are expected to provide inputs for the development of competency-based economic education management in IPS.